Synthesis of Carbon-Silica Nanomaterials by Carbonization of Cellulose Acetate and Polyisocyanate Copolymer - Goncharuk, V.V.; Dubrovin, I.V.; Dubrovina, L.V.; Kucheruk, D.D.; Naboka, O.V.; Ogenko, V.M. (Physics and Chemistry of Solid State, 2016)
Cellulose acetate and polyisocyanate copolymer synthesized by mechanical mixing of cellulose acetate, polyisocyanate and fumed silicon dioxide in the presence of nickel chloride was carbonized in silicon dioxide template. Copolymer and silicon dioxide template were formed simultaneously. Composite structure and composition was studied with SEM and EDS. SEM showed that porous carbonaceous nanomaterial was synthesized. Formed carbon is represented by coating on silicon dioxide, layered ribbon-like and fibrous structures in template pores with size from several nm (thickness) to several microns (length). Metallic nickel crystals up to 200 nm in size were fabricated in composite pores from Nickel chloride by reduction of Ni2 with products of pyrolysis of organic compounds.